2001
DOI: 10.1002/1097-4628(20010411)80:2<242::aid-app1092>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactions and polymerization of hexa-[3-tert-butyl-4- hydroxyphenoxy]cyclotriphosphazene: A new method for the preparation of soluble cyclomatrix phosphazene polymers

Abstract: Novel cyclomatrix phosphazene‐containing polyester polymers were synthesized through the reaction of a polyhydroxylated cyclotriphosphazene and a bifunctional acid chloride. To demonstrate the chemistry of the free hydroxyl of hexa‐[3‐tert‐butyl‐4‐hydroxyphenoxy]cyclotriphosphazene, nucleophilic displacement reactions were performed with both acetic anhydride and alkyl chlorides. This work compares favorably to literature data for the chemistry of hexa‐[4‐hydroxyphenoxy]cyclotriphosphazene, whose hydroxyl is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A recent study reported the preparation of cyclomatrix materials utilizing 1 and 2 as precursors 19. The steric hindrance associated with the tert ‐butyl group adjacent to the reactive hydroxyl site resulted in longer reaction times for the addition of organic crosslinkers to 2 compared to the reaction times with 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported the preparation of cyclomatrix materials utilizing 1 and 2 as precursors 19. The steric hindrance associated with the tert ‐butyl group adjacent to the reactive hydroxyl site resulted in longer reaction times for the addition of organic crosslinkers to 2 compared to the reaction times with 1 .…”
Section: Introductionmentioning
confidence: 99%